The Influence of Self-Control Through Self-Efficacy on Academic Procrastination - Yuliana, Yuliana; Eddy Wibowo, Mungin; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2022)
Academic procrastination is a vital concern, considering that it has detrimental effects on students, like emotional disturbances (stress, anxiety disorders, self-guilt, depression and disappointment), academic performance, social achievement, subjective well-being, and even physical health. This study aims to prove that self-efficacy can mediate the effect of self-control on academic procrastination. The sample was taken using the random cluster sampling technique consisting of 329 students from 4 schools in Semarang. The data analysis technique used was bias-corrected bootstrapping. The findings proved that self-control predicts self-efficacy, while self-control and self-efficacy predict academic procrastination. Moreover, self-control can reduce academic procrastination through self-efficacy. This study's results indicated that self-control and self-efficacy are essential and significantly minimize academic procrastination.